2010
DOI: 10.3892/ol_00000022
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative infections are associated with adverse outcome after resection with curative intent for colorectal cancer

Abstract: Abstract. this study focused on the impact of post-operative infection on patient outcome after resection with curative intent for colorectal cancer. Postoperative surgical and medical complications have been implicated as a negative predictor of long-term outcome in various malignancies. We studied a population of 1083 patients who underwent resection with curative intent for colorectal cancer. these patients were divided into 2 groups based on the occurrence (65 patients, 6%) or absence (1018 patients, 94%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…Although hypovolemia in the absence of surgical stress did lead to an increase in pulmonary metastases, our findings demonstrate that neither severe intraoperative hypovolemia nor hypothermia impact the prometastatic effects of surgical stress. Correlative clinical studies confirm that postoperative infections following surgery can accelerate the time to cancer recurrence [ 45 47 ]. Here, using murine models we demonstrate that polymicrobial sepsis in conjunction with surgical stress facilitates the development of perioperative lung metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Although hypovolemia in the absence of surgical stress did lead to an increase in pulmonary metastases, our findings demonstrate that neither severe intraoperative hypovolemia nor hypothermia impact the prometastatic effects of surgical stress. Correlative clinical studies confirm that postoperative infections following surgery can accelerate the time to cancer recurrence [ 45 47 ]. Here, using murine models we demonstrate that polymicrobial sepsis in conjunction with surgical stress facilitates the development of perioperative lung metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Following screening of titles and abstracts, 25 papers were retrieved in full‐text form and assessed for eligibility. All 25 articles reported the effects of postoperative complications on long‐term survival; however, eight of these were of poor methodological quality as judged by a NOS score of 6 or less and were therefore excluded ( Tables S1 and S2 , supporting information). Poor NOS scores were due to inadequate or unreported follow‐up, lack of patient demographic information, and lack of appropriate controls for confounding factors (such as use of unadjusted univariable regression models).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of excluded poor‐quality studies was assessed by a further sensitivity analysis. Of eight excluded studies, three reported HRs suitable for analysis ( Table S3 , supporting information). Inclusion of these in meta‐analysis had no effect on findings for overall survival, with similar results for all complications (HR 1·29, 1·22 to 1·36; P < 0·001) and infectious complications (1·52, 1·42 to 1·62; P < 0·001).…”
Section: Resultsmentioning
confidence: 99%
“…Although hypovolemia in the absence of surgical stress did lead to an increase in lung metastases our findings demonstrate that neither severe intraoperative hypovolemia nor hypothermia impact the prometastatic effects of surgical stress. Correlative clinical studies confirm that postoperative infections following surgery can accelerate the time to cancer recurrence [46][47][48] . Here, using murine models we demonstrate that polymicrobial sepsis in conjunction with surgical stress facilitates the development of perioperative lung metastases.…”
Section: Discussionmentioning
confidence: 99%